Burden and trend of maternal sepsis and other maternal infections in BRICS countries from 1990 to 2021 - Jiao Long; Qi Zhang; Chao Ma (BMC Pregnancy and Childbirth)
Abstract Background Maternal septicemia and other maternal infections (MSMIs) continue to pose considerable challenges to public health on a global scale. However, comprehensive data on their impacts and trends are limited, particularly in BRICS countries, which include Brazil, Russian Federation, India, China, and South Africa. This study aims to compare the global epidemiological trends of MSMIs from 1990 to 2021 to MSMIs trends in BRICS countries and examine the relationship of disease burden with age and social development. Methods Using data from the Global Burden of Disease database, this study analyzed the prevalence, incidence, death, and disability-adjusted life years (DALYs) of MSMIs from 1990 to 2021 globally and in BRICS countries. Temporal trends were assessed through estimated annual percentage change (EAPC) and percentage change. Joinpoint regression analysis was employed to rigorously evaluate time trends, allowing for the calculation of annual percentage change (APC) and average annual percentage change (AAPC), with corresponding 95% confidence intervals (CI). Results In 2021, South Africa showed the highest prevalence of MSMIs (156.54 per 100,000), while the Russian Federation exhibited the highest incidence (1,001.51 per 100,000). Deaths and DALYs of MSMIs were lowered in BRICS countries compared to global averages. Between 1990 and 2019, India experienced the greatest decline in both incidence (EAPC = -2.68%) and prevalence (EAPC = -2.65%). Despite the global decline, regional variations in incidence were observed. In China, the incidence increased significantly between 2010 and 2014 (APC = 4.15%; 95% CI: 3.59–4.71%; P < 0.001). Similarly, in the Russian Federation, the incidence rose during three distinct periods: 2000–2004 (APC = 2.52%; 95% CI: 2.0–3.05%; P < 0.001), 2004–2010 (APC = 5.2%; 95% CI: 4.95–5.44%; P < 0.001), and 2010–2015 (APC = 1.79%; 95% CI: 1.46–2.12%; P < 0.001). Conclusion MSMIs remain prevalent globally, imposing a substantial disability burden, particularly in BRICS countries. While China exhibits relatively low disease burdens, South Africa faces high prevalence, and global deaths and DALYs from MSMIs remain elevated.